Christopher Brumfit Ph.D./Ed.D. Thesis Award 2012. (24th September 2013) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> The Editor and Board of Language Teaching are pleased to announce that the winner of the 2012 Christopher Brumfit thesis award is Dr Jim Ranalli. The thesis was selected by an external panel of judges based on its significance to the field of second language acquisition, second or foreign language learning and teaching, originality and creativity and quality of presentation.